Rate-Independent Linear Damping for the Improved Seismic Performance of Inter-Story Isolated Structures. Issue 2 (25th January 2022) - Keivan, Ashkan; Zhang, Ruiyang; Keivan, Darioush; Phillips, Brian M.; Ikenaga, Masahiro; Ikago, Kohju
ABSTRACT: In this study, rate-independent linear damping (RILD) is proposed for the seismic protection of inter-story isolated structures. For practical applications, the RILD force is approximated using a causal algorithm and then tracked using semi-active control. Both numerical simulation and shake table real-time hybrid simulation (RTHS) are used to study a 14-story inter-story isolated structure. First, the causal approximation of RILD evaluated in RTHS is compared to numerical simulation. Second, the benefits of RILD for inter-story isolated structures are demonstrated as compared to conventional damping. RILD offers an attractive control alternative by restricting isolation layer displacements without amplifying accelerations.